2019
DOI: 10.1016/j.conbuildmat.2018.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rapid hardening recycled clean steel fibre materials

Abstract: This is a repository copy of Performance of rapid hardening recycled clean steel fibre materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Caggianoa et al [16] studied the mechanical properties of hybrid fiber concrete by mixing industrial steel fiber (ISF) and recycled steel fiber (RSF) with different contents into concrete. It is found that the geometric characteristics of RSF depend on the sources and processing methods of waste tires.…”
Section: Foreign Research Resultsmentioning
confidence: 99%
“…Caggianoa et al [16] studied the mechanical properties of hybrid fiber concrete by mixing industrial steel fiber (ISF) and recycled steel fiber (RSF) with different contents into concrete. It is found that the geometric characteristics of RSF depend on the sources and processing methods of waste tires.…”
Section: Foreign Research Resultsmentioning
confidence: 99%
“…H. Al-musawi, et al [52] investigated the flexing performance of fast-setting mortar mixes made with two types of commercial cement, calcium sulfonate cement and CAC, for thin concrete repair applications. They performed three-point bending tests on samples of smooth steel-fiber reinforced (FRC) concrete containing 45 kg/m 3 of recycled clean steel fibers to characterize the bending performance of notched and notched prisms at different ages, ranging from one hour to one year.…”
Section: Cac + Recyclingmentioning
confidence: 99%
“…When RSF was increased from 0.35 percent to 0.70 percent in specimen four for the same-size (50 mm long and 0.15 mm thick) RSF, a 13 percent enhancement in FS was detected [ 52 ]. In comparison to specimen one, employing about double the amount (0.57 percent by volume fraction) of shorter RSF (21 mm long) resulted in a considerable increase of 69% and 31% in flexure strength of specimens two and three, respectively [ 68 ]. A substantial increase in FS was reported when utilizing RSFs that had lengths of 21 mm and 50 mm and diameters of 0.15 mm and 0.20 mm from 0.35% to 0.70%.…”
Section: Properties Of Rsf-incorporated Mortarsmentioning
confidence: 99%